2011
DOI: 10.5751/ace-00483-060206
|View full text |Cite
|
Sign up to set email alerts
|

Patch Scale Nest-Site Selection by Marbled Murrelets (Brachyramphus marmoratus)

Abstract: ABSTRACT. The Marbled Murrelet (Brachyramphus marmoratus) is a threatened alcid that nests almost exclusively in old-growth forests along the Pacific coast of North America. Nesting habitat has significant economic importance. Murrelet nests are extremely difficult and costly to find, which adds uncertainty to management and conservation planning. Models based on air photo interpretation of forest cover maps or assessments by low-level helicopter flights are currently used to rank presumed Marbled Murrelet nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The attraction of Woodpigeons for taller trees has often been reported , Rouxel & Czajkowski 2004, although this has been virtually unstudied quantitatively. Tall trees may permit escape from human persecution (Dutta 2007, Hanane & Baâmal 2011 and may also provide a distinct landmark to help commuting adults in locating the nest (Silvergieter & Lank 2011). Furthermore, the presence of livestock (sheep and goats) seems to affect the selection of nest-tree by Woodpigeons in the study area.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The attraction of Woodpigeons for taller trees has often been reported , Rouxel & Czajkowski 2004, although this has been virtually unstudied quantitatively. Tall trees may permit escape from human persecution (Dutta 2007, Hanane & Baâmal 2011 and may also provide a distinct landmark to help commuting adults in locating the nest (Silvergieter & Lank 2011). Furthermore, the presence of livestock (sheep and goats) seems to affect the selection of nest-tree by Woodpigeons in the study area.…”
Section: Discussionmentioning
confidence: 98%
“…Nest-site selection by birds results from a series of behavioural choices (Silvergieter & Lank 2011). Nestsites in birds may offer the basic needs of breeding adults, eggs and young, including a suitable substratum, protection from inclement weather (Sadoti 2008) and predators (Hatchwell et al 1999), and proximity to food sources (Wiehn & Korpimäki 1997).…”
mentioning
confidence: 99%
“…At the patch level, Manley (1999) found no evidence of selection for the size or types of gaps in a patch. Other researchers have found measures of vertical complexity to be positively related to likelihood of nesting (Conroy et al 2002, Waterhouse et al 2002, Silvergieter and Lank 2011a, numbers of occupied behaviors observed Newsom 2002, Burger andBahn 2004), and likelihood of occupancy (Hamer et al 2008).…”
Section: Patch Scalementioning
confidence: 96%
“…One radio-telemetry study examined the difference between successful versus unsuccessful nests (Bradley 2002) at a landscape scale. Although landscape scale habitat data may be easier to obtain, landscape-only models received less support compared with models that incorporated patch scale variables measured from the ground (Silvergieter and Lank 2011a). Several other habitat preference studies used number of murrelet detections from ground surveys to make comparisons at the stand scale (Miller and Ralph 1995, Burger and Bahn 2004, COSEWIC 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation